Technology organization environment framework in cloud computing - Iqbal Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Cloud Computing is a rapidly emerging technology over the last few years, that has abolished the burden of purchasing heavy hardware and software. Cloud computing has been advantageous to Small and Medium-sized Enterprises (SMEs), though many SMEs have not adopted to delve into its appealing benefits. To increase the cloud adoption rate in these Enterprises, the most important thing is to understand the aspects which influence the cloud adoption. The article focuses on these factors, which influence the use of cloud services by establishing the three layer hierarchical framework based on the grounded on the Technology Oriented Environmental (TOE) framework through systematic literature review. Because cloud-based solutions offer numerous benefits for companies, they have precious cloud determinants. This paper therefore took into account the Technology Organization Environment TOE model for Cloud Computing adoption. In addition, the questionaries designed at the end also indicate the significant connection in the decision of adoption between three context of TOE. Moreover, the designed questionaries has been used for the analysis of cloud computing adoption in Bangladeshi SMEs.